Zinc amino acid complex in association with chromium methionine improves the feed efficiency of finished Nellore cattle in the feedlot - Vellini, Beatriz L. [UNESP]; Prados, Laura F.; Monção, Flávio P. [UNESP]; Fireman, Alba K.; Resende, Flávio D. [UNESP]; Siqueira, Gustavo R. [UNESP] (Elsevier, 2020)
Trace minerals are vital to the metabolism and performance of beef cattle and may improve meat quality. The objective of this study was to evaluate the effects of a Zn amino acid complex (ZnAA) fed alone or in association with a Cr methionine complex (CrMet) on the performance and meat quality of Nellore cattle finished in a feedlot. Three hundred thirty-six Nellore bulls were blocked by body weight (BW; 342 ± 24.5 kg) and assigned to one of the following three dietary treatments: a control diet containing 54 mg/kg of Zn from an inorganic source of minerals (CON); a diet providing 21.6 mg/kg of Zn from an inorganic source with 32.4 mg/kg of a Zn amino acid complex (ZnAA); and a diet providing 21.6 mg/kg of Zn from an inorganic source with 32.4 mg/kg of a Zn amino acid complex combined with 0.36 mg/kg of a CrMet complex (ZnCr). The total number of days on the diets was 130 days, with an initial 35-d period for dietary acclimation to the finishing diet. Statistical analysis was performed using the MIXED procedure of SAS with the pen as the experimental unit (36 pens). Blood parameters and meat quality were analyzed as repeated measures (from 72 animals; 2 animals/pen). The final BW, dry matter intake (DMI), and average daily gain (ADG) was similar among the treatments (P ≥ 0.261). The overall mean DMI, final BW, and ADG were 9.15 kg/d, 535 kg, and 1.49 kg/d, respectively. Feeding ZnCr improved efficiency (P = 0.011) compared with the ZnAA and CON bulls. Leucocytes, aminotransferase, β-hydroxybutyric acid, cholesterol, glucose, and cortisol were affected (P ≤ 0.038) by time but not by dietary treatment. Flight speed and serum cortisol level were unaffected (P ≥ 0.518) by dietary treatment. No significant treatment effects (P ≥ 0.169) were detected for hot carcass weight, fat, pH, temperature, liver, kidney, or KPH. Treatment tended to alter the area of the Longissimus muscle (P = 0.081). The Longissimus muscle area was greater for bulls fed ZnCr than for bulls fed ZnAA or CON (80.6 vs. 77.5 cm2). There was a tendency (P = 0.073) for decreased Warner-Bratzler shear force in animals fed ZnCr. Tenderness was improved by 12.3 % compared with CON. Individual fatty acids (P ≥ 0.171) and total fatty acids (saturated and unsaturated; P ≥ 0.392) did not differ among the treatments. These data suggest that finishing Nellore bulls fed ZnCr in a feedlot setting exhibited greater efficiency and tended to exhibit improved meat tenderness compared with bulls fed ZnAA.
Keywords: Chromium; Complexed minerals; Meat quality; Nellore; Trace mineral; Zinc